2020
DOI: 10.1111/fwb.13615
|View full text |Cite
|
Sign up to set email alerts
|

Seed dispersal by neotropical waterfowl depends on bird species and seasonality

Abstract: 1. Waterbird-mediated endozoochory is an essential mechanism for the dispersal of sessile organisms in freshwater ecosystems. However, in the neotropics there are no previous studies of how different waterbird species vary in the dispersal functions they perform, and how seasonality influences endozoochory. In this study, we identified plant diaspores dispersed in faeces of five South American waterfowl (Brazilian teal Amazonetta brasiliensis, yellow-billed teal Anas flavirostris, ringed teal Callonetta leucop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 60 publications
1
40
1
Order By: Relevance
“…Unlike most homosporous ferns, which disperse their spores via air currents (Barrington, 1993), spore dispersal in Isoëtes is poorly understood because they are aquatic and produce large megaspores (200-1000μm), unable to be dispersed by wind. Anecdotal evidence suggests they can be dispersed by waterways, waterfowl, or even snails and earthworms (Duthie, 1929; Jermy, 1990; Taylor & Hickey, 1992; Larsén & Rydin, 2016), and recent work has documented spores in waterfowl fecal matter (Silva et al , 2020), confirming previous observations. It is not inconceivable that sporangia, spores, or even whole plants are dispersed in the crops of these migratory animals (Les et al , 2003).…”
Section: Discussionsupporting
confidence: 75%
“…Unlike most homosporous ferns, which disperse their spores via air currents (Barrington, 1993), spore dispersal in Isoëtes is poorly understood because they are aquatic and produce large megaspores (200-1000μm), unable to be dispersed by wind. Anecdotal evidence suggests they can be dispersed by waterways, waterfowl, or even snails and earthworms (Duthie, 1929; Jermy, 1990; Taylor & Hickey, 1992; Larsén & Rydin, 2016), and recent work has documented spores in waterfowl fecal matter (Silva et al , 2020), confirming previous observations. It is not inconceivable that sporangia, spores, or even whole plants are dispersed in the crops of these migratory animals (Les et al , 2003).…”
Section: Discussionsupporting
confidence: 75%
“…See Table 1 for full names of bird species. Silva G. G. et al, 2021) showing that differences in the species composition of seeds dispersed by waterfowl species are related to their foraging behavior (note, these studies did not consider plant traits). In contrast, a study of other waterbirds in rice fields found no difference between a gull and stork species in the plants they dispersed (Martín-Vélez et al, 2021).…”
Section: Different Waterfowl Have Different Roles As Seed Vectorsmentioning
confidence: 99%
“…Interactions between plants and frugivorous birds (i.e., those feeding on fleshy-fruits) in terrestrial ecosystems are known to depend on many traits of both groups of organisms, such as fruit size and palatability and bill morphology (Wenny et al, 2016;Donoso et al, 2017). On the other hand, despite recent advances in identifying the interactions between different waterfowl and plant species in a particular community (Reynolds and Cumming, 2016;Sebastián-González et al, 2020;Silva G. G. et al, 2021), the trait associations underlying the uptake of seeds by different waterfowl species remain unknown. In general, seed ingestion by non-frugivorous vertebrates is not size limited in a manner comparable to frugivores (Chen and Moles, 2015; but see Gurd, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of birds can aid in directed and long-distance movement of bryophytes as they may act as dispersers in local sites through foraging and nesting (Calvelo et al, 2006;Parnikoza et al, 2012;Amélio et al, 2017;Parnikoza et al, 2018), and transcontinentally through migratory movements (Chmielewski & Eppley, 2019). Birds can disperse bryophytes long distances via ectozoochory, by external transportation (Lewis et al, 2014), and may be able to do this via endozoochory, through internal ingestion, as has also been shown with ferns and other herbs (Lovas-Kiss et al, 2018;Blanco et al, 2019;Hervías-Parejo et al, 2019;Silva et al, 2020).…”
Section: Introductionmentioning
confidence: 87%